2021
DOI: 10.52547/jfl.9.38.205
|View full text |Cite
|
Sign up to set email alerts
|

Pronunciation Achievement in Computer-Mediated Communication (CMC) Classrooms

Abstract: The current mixed method study investigated the use of synchronous/asynchronous computermediated communication as a method of L2 pronunciation achievement among medical students during COVID-19 pandemic lockdown. In so doing, the study utilized an experimental comparative design with two groups of 17 participants. There were two types of tests in this study: word stress test, and a semi-structured interview. The results showed the positive effect of computer mediated communication in pronunciation development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 35 publications
2
5
0
Order By: Relevance
“…The more time students spent at home taking virtual sessions, the more they advocated for synchronous sessions. These results are in line with those studies that endorse a balance of both asynchronous and synchronous activities, and/or a deep analysis of the students' needs to assure learning when taking courses online (Hodges et al, 2020;Moser et al, 2021;Quesada Vázquez, 2021;Rapanta et al, 2020;Zeinali et al, 2021a). Nevertheless, only 25% of the students who took the pronunciation courses online participated in the study.…”
Section: Conclusionessupporting
confidence: 89%
See 4 more Smart Citations
“…The more time students spent at home taking virtual sessions, the more they advocated for synchronous sessions. These results are in line with those studies that endorse a balance of both asynchronous and synchronous activities, and/or a deep analysis of the students' needs to assure learning when taking courses online (Hodges et al, 2020;Moser et al, 2021;Quesada Vázquez, 2021;Rapanta et al, 2020;Zeinali et al, 2021a). Nevertheless, only 25% of the students who took the pronunciation courses online participated in the study.…”
Section: Conclusionessupporting
confidence: 89%
“…SCMC seemed to boost students' learning process, as lectures activated students' interplay and reinforced teacher-learner communication, which allowed collaborative learning, extemporaneous discussion and instant feedback. These findings reinforced Zeinali et al (2021a;2021b), who found synchronous pronunciation teaching more effective than F2F or ACMC, and further underpins other studies that highlight the social presence of the teacher in distance learning (Juárez Díez & Hinojosa Hernández, 2021;Lin, 2015;Nguyen, 2020). ACMC measures, such as narrated PowerPoint presentations, were also highly rated.…”
Section: Conclusionessupporting
confidence: 81%
See 3 more Smart Citations